Penerapan Metode Key Performance Indicator Dalam Penilaian Kinerja Sales Sari Roti Cabang Bengkulu - Dewangga, Danang Wisnu; Yulianti, Liza; Trianggana, Dimas Tri (Jurnal Media Infotama, 2025)
PT Indosari Niaga Nusantara Bengkulu Branch is one of the bread companies in Bengkulu Province, also known as Sari Roti, which sells various types of halal, quality, safe for consumption and affordable bread for the community. So far, the performance appraisal is still using a paper performance appraisal form which is then inputted again to make a performance appraisal report. This certainly takes a long time and the lack of efficiency of the Company's HRD department in providing performance evaluation results, especially bread sales. The application of the Key Performance Indicator Method in the performance appraisal of Sari Roti Bengkulu Branch sales can help facilitate the management of Sari Roti sales data and sales performance appraisal data, can assist in providing information on the results of the evaluation of sales performance appraisal every assessment period, and can be used as a basis for evaluating sales performance every assessment period. Based on the test data used as many as 15 bread sales in the July-September assessment period of 2023, it was found that the results of the evaluation of Sari Roti Bengkulu Branch sales performance were very good as many as 12 sales, good as many as 1 sales, and quite good as many as 2 sales.